Cardiovascular effects of the combined exposure to noise and outdoor air pollution: A review - Lekaviciute, J; De Kluizenaar, Y; Laszlo, H; Hansell, A; Floud, S; Lercher, P; Babisch, W; Kephalopoulos, S (2012)
The combination of noise with other environmental stressors, particularly traffic-related air pollution, has been of growing interest in recent years. Cardiovascular effects are among the most evidence-based physical health outcomes. Moreover, the European Network on Noise and Health (ENNAH), which helped to establish collaboration between researchers on noise and researchers on air quality, identified gaps in the evidence of environmental noise related health research and concluded that one of the most important topics to focus on was noise and co-exposures. Therefore, the objective of this paper is to summarize current knowledge on the association between environmental noise and air pollutant exposure and cardiovascular health effects, and to look at whether the evidence suggests that noise and air pollution confound or interact with each other. This review comprises a literature search for the period 2005 to 2012. It also aims to identify gaps which could help to shape future research directions. The results suggest that noise and air pollution exert independent effects on cardiovascular health, but the evidence for any interactive effects is still limited and has to be further investigated.